Characteristics of Residence Time of the Torrefaction Process on the Results of Pruning Kesambi Trees - Jemmy Jonson Sula Dethan; Fredrik Julius Haba Bunga; Mellissa Erlyn Stephanie Ledo; Jemseng Carles Abineno (The University of Lampung, 2024)
The excessive use of Kesambi (Schleichera oleosa) tree stems threatens the sustainability of Kesambi plants since it takes several decades for them to regenerate new stems. This research aims to determine the characteristics of torrefied Kesambi tree pruning. The used reactor has a diameter of 400 mm. An iron basket is positioned 100 mm above the reactor base, holding the material within an aluminum cylinder. The reactor temperature is maintained at 300°C using a K-type thermocouple sensor. A heater is placed near the reactor base and covered. The characteristics of the semi-charcoal biomass product are identified, including mass yield, water absorption capacity, moisture content (D3173, 2013); ash content (ASTM D1102-84. Standard Test Method for Ash in Wood, 2013); volatile matter (%) (ASTMD3175, 2011); and fixed carbon (%) (ASTM, 2013). The color of the leaves and the pruned Kesambi tree changes from brown to black as the residence time increases. The results of pruning the Kesambi tree at different torrefaction residence times indicate a decrease in mass yield with an increase in residence time, with the lowest mass yield observed at a residence time of 20 minutes. The water absorption capacity of torrefied Kesambi tree pruning material is found to be between 0.65% and 0.675%, or less than 1% and higher heating value (HHV) prediction 29.0750 MJ/kg.Keywords: Kesambi, Pruning, Residence, Time, Torrefaction